2000
DOI: 10.1002/1096-9861(20001204)428:1<145::aid-cne10>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory projections in a chondrostean fish,Acipenser baeri: An experimental study

Abstract: The presence of extrabulbar primary olfactory projections has been well established in teleosts. In order to investigate the phylogeny of these projections and to compare their targets with those of the secondary olfactory projections, the connections of the olfactory epithelium and olfactory bulb were studied by means of tract-tracing methods in a chondrostean, Acipenser baeri. Primary olfactory projections mainly extend to the glomerular layer of the olfactory bulb, but a significant number of extrabulbar ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(2 citation statements)
references
References 64 publications
(196 reference statements)
2
0
0
Order By: Relevance
“…This study also showed that the lateral olfactory tract specifically innervates the habenula while the medial olfactory tract also sends projections to the Vv. These projection patterns have been confirmed by anatomical tracing studies in other fish species (Huesa et al, 2000; Folgueira et al, 2004; Northcutt, 2011). In zebrafish, the mitral cells are shown to project to Vv and the dorsal-posterior part of the telencephalon (Dp) and to the right habenula and the hypothalamus in the diencephalon (Rink and Wullimann, 2004; Miyasaka et al, 2009; Gayoso et al, 2011).…”
Section: The Olfactory Bulb: Primary Processing Of Odor Informationsupporting
confidence: 67%
“…This study also showed that the lateral olfactory tract specifically innervates the habenula while the medial olfactory tract also sends projections to the Vv. These projection patterns have been confirmed by anatomical tracing studies in other fish species (Huesa et al, 2000; Folgueira et al, 2004; Northcutt, 2011). In zebrafish, the mitral cells are shown to project to Vv and the dorsal-posterior part of the telencephalon (Dp) and to the right habenula and the hypothalamus in the diencephalon (Rink and Wullimann, 2004; Miyasaka et al, 2009; Gayoso et al, 2011).…”
Section: The Olfactory Bulb: Primary Processing Of Odor Informationsupporting
confidence: 67%
“…The lateral portion of the pallium receives primary projections from the olfactory epithelium via the olfactory bulbs (Bleckmann et al, 1987;Smeets & Northcutt, 1987). The secondary olfactory projections, divided into a lateral and a medial tract, are similar to those observed in other vertebrates, including agnathans (Northcutt & Puzdrowski, 1988;Wicht & Northcutt, 1993;Wicht, 1996), amphibians (ten Donkelaar, 1998a, b;Dicke & Roth, 2007) and teleosts (Huesa et al, 2000;Northcutt, 2006). The larger of the two, the lateral tract, terminates most heavily in the lateral pallium of chondrichthyans (Hofmann & Northcutt, 2008).…”
Section: T E L E N C E P H a L O Nsupporting
confidence: 53%